A New Assessment Framework for Transience in Hydrogeological Systems. Issue 1 (10th December 2014) - Currell, Matthew; Gleeson, Tom; Dahlhaus, Peter
Abstract: The importance of transience in the management of hydrogeologic systems is often uncertain. We propose a clear framework for determining the likely importance of transient behavior in groundwater systems in a management context. The framework incorporates information about aquifer hydraulics, hydrological drivers, and time scale of management. It is widely recognized that aquifers respond on different timescales to hydrological change and that hydrological drivers themselves, such as climate, are not stationary in time. We propose that in order to assess whether transient behavior is likely to be of practical importance, three factors need to be examined simultaneously: (1) aquifer response time, which can be expressed in terms of the response to a step hydrological change ( τstep ) or periodic change (τcycle ); (2) temporal variation of the dominant hydrological drivers, such as dominant climatic systems in a region; (3) the management timescale and spatial scale of interest. Graphical tools have been developed to examine these factors in conjunction, and assess how important transient behavior is likely to be in response to particular hydrological drivers, and thus which drivers are most likely to induce transience in a specified management timeframe. The method is demonstrated using two case studies; a local system that responds rapidly and is managed on yearly to decadal timeframes and a regional system that exhibits highly delayed responses and was until recently being assessed as a high level nuclear waste repository site. Any practical groundwater resource problem can easily be examined using the proposed framework.